3D Printed Personalized Guide Plate in the Femoral Head Core Decompression. (19th November 2020) - Cheng, Liangliang; Qiu, Xing; Yang, Lei; Xiao, Chi; Liu, Baoyi; Okoye, Chukwuemeka Samuel; Zhao, Dewei
Abstract : Objective . To investigate the feasibility of using 3D printed personalized guide plates in core decompression procedures for the treatment of osteonecrosis of the femoral head (ONFH). Methods . The clinical data of 8 patients undergoing femoral head core decompression from January to December 2019 were analyzed retrospectively. Three-dimensional (3D) images of the patients were reconstructed from the CT scan data taken preoperatively. From the data obtained, puncture position, drill hole, and depth were evaluated, and individualized 3D puncture guide plates were designed using Mimics 21.0 software. During the operation, the needle went through the hole of the guide plate, the depth of the drill was controlled, and the obtained bone tissues were sent for pathological evaluation. Intraoperative X-ray and postoperative pathological results were used to evaluate the success of the puncture. Results . The individualized guide plates used for core compression on the 8 patients were well fitted with the anatomic structure of the puncture site, and the direction and depth of the needle insertion were consistent with the preoperative design. The operation time was about 15-22 mins. The position of the decompression tunnel was the same as the designed plate. The postoperative pathology showed necrotic bone tissue. There were no postoperative complications such as infection, bleeding, and fracture. Conclusion . The 3D printed individualized guide plate can simplify core decompression and would make this procedure more accurate, safe, and quick, in addition to obtaining necrotic tissues for pathological examination.